A study to assess the influence of interprofessional point of care simulation training on safety culture in the operating theatre environment of a university teaching hospital. Issue 2 (3rd March 2016) - Hinde, Theresa; Gale, Thomas; Anderson, Ian; Roberts, Martin; Sice, Paul
ABSTRACT: Interprofessional point of care or in situ simulation is used as a training tool in our operating theatre directorate with the aim of improving crisis behaviours. This study aimed to assess the impact of interprofessional point of care simulation on the safety culture of operating theatres. A validated Safety Attitude Questionnaire was administered to staff members before each simulation scenario and then re-administered to the same staff members after 6–12 months. Pre- and post-training Safety Attitude Questionnaire—Operating Room (SAQ-OR) scores were compared using paired sample t-tests. Analysis revealed a statistically significant perceived improvement in both safety ( p < 0.001) and teamwork ( p = 0.013) climate scores (components of safety culture) 6–12 months after interprofessional simulation training. A growing body of literature suggests that a positive safety culture is associated with improved patient outcomes. Our study supports the implementation of point of care simulation as a useful intervention to improve safety culture in theatres.